2020
DOI: 10.5606/tr-ent.2020.36349
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of frontal cells according to the International Frontal Sinus Anatomy Classification

Abstract: Objectives: This study aims to determine the regional frequency of frontal cells classified by the International Frontal Sinus Anatomy Classification (IFAC) in local population radiologically. Patients and Methods: Between February 2018 and May 2019, a total of 300 frontal recess regions of 150 adults (88 males, 62 females; mean age 33.5±9.4 years; range, 18 to 54 years) eligible for the inclusion criteria and undergoing paranasal sinus (PNS) computed tomography (CT) were included in the study. In CT analysis;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Much effort has been made to define and classify these cells, which have recently shown their effect on frontal sinus drainage, with IFAC describing the pneumatization pattern of the ethmoid and frontal sinuses (12,15). This classification system was developed as a clinical guide to provide a more anatomically accurate description of pneumatization patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much effort has been made to define and classify these cells, which have recently shown their effect on frontal sinus drainage, with IFAC describing the pneumatization pattern of the ethmoid and frontal sinuses (12,15). This classification system was developed as a clinical guide to provide a more anatomically accurate description of pneumatization patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the clinical applicability and importance of IFAC, it has been reported that >65% of the residents included in the study found IFAC clinically applicable, and >70% saw it as a tool that helps in consistent communication between surgeons, and 65.6% agreed that it is necessary to understand the classification system. 15 However, it was emphasized that IFAC needs to be supported by intraoperative findings and should be studied with large samples (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the anterior ethmoid and frontal sinus is complex, but improvements in imaging technology are helping us to understand these spaces more clearly. Many recent reports have identified and classified the cells of the anterior ethmoid and frontal sinus based on their location [1][2][3][4][5]. However, the drainage pathways of the frontoethmoidal region are variable and their paths tortuous due to multiple bony walls which form the pathways.…”
Section: Introductionmentioning
confidence: 99%